The boy ebook A novel. - Hoag, Tami (Broussard and Fourcade, 2018)
Now a New York Times bestseller An unfathomable loss or an unthinkable crime? #1 New York Times bestselling author Tami Hoag keeps you guessing in her most harrowing thriller yet.   When Detective Nick Fourcade enters the home of Genevieve Gauthier outside the sleepy town of Bayou Breaux, Louisiana, the bloody crime scene that awaits him is both the most brutal and the most confusing he's ever seen. Genevieve's seven-year-old son, KJ, has been murdered by an alleged intruder, yet Genevieve is alive and well. Meanwhile, Nick's wife, Detective Annie Broussard, sits with the grieving Genevieve. A mother herself, Annie understands the devastation this woman is going through, but as a detective she's troubled: Who would murder a child and leave the only witness behind?   When KJ's babysitter, twelve-year-old Nora Florette, is reported missing the very next day, the town fears a maniac is preying on their children. With pressure mounting from a tough, no-nonsense new sheriff, the media, and the parents of Bayou Breaux, Nick and Annie dig deep into the dual mysteries. Is someone from Genevieve's past or present responsible for the death of her son? Is Nora a victim, or something worse? Then everything changes when Genevieve’s past as a convicted criminal comes to light. Could she have killed her own child to free herself from the burden of motherhood, or is the loss of her beloved boy pushing her to the edge of insanity? Could she have something to do with the disappearance of Nora, or is the troubled teen the key to the murder? How far will Nick and Annie have to go to uncover the dark truth of the boy?